Rancang Bangun Sistem Informasi Sekolah Berbasis Website (Studi Kasus : SDIT Azzhahiriyah) - Naufal Muyassar; Wahyu Hadikristanto; Muhamad Fatchan (Prosiding Sains dan Teknologi, 2022)
The progress of science and technology at this time shows that speed, convenience, and security are the main considerations and benchmarks in facing global challenges. Information systems must be able to be effective and efficient in providing a series of information flow processes to improve the quality and quantity and satisfaction of clients or work partners. "Designing Website-Based School Information System (Study: SDIT Azzhahiriyah)" is a problem that exists in schools, namely the provision of information from schools to the community. The purpose of this research is to make it easier to disseminate school information in disseminating information from the school side and school activities, see contacts or contact schools. In the design the author uses phpmysql and xampp. This manufacturing process uses the waterfall method. This research shows that the existence of a website-based information system will make it easier to find out school information. Keywords: Design, Information System, Waterfal, Website